Use Of Protective Tools In Learning Mathematics In Elementary Schools - Juli Asmida Rambe; Rapita Rapita (STABN RADEN WIJAYA WONOGIRI, 2025)
Study This aim For describe How use tool props in learning process mathematics in School Base (SD). Mathematics school is mathematics which has sorted And customized with stage development intellectual student, and is used as a means to develop students' thinking skills. Mathematics is object Which nature abstract so that mathematics No easy understood by some student School Base. Use tool props expected can help in improving students' understanding of mathematical concepts. Thus, mathematics as an abstract object can be reduced in its abstractness by using concrete object models called mathematical learning aids. These aids can function in learning mathematics that is, motivating student in process Study and new relationships. The benefits of teaching aids are that they can improve children's motoric sensors, reduce method learning Which nature verbalism, increase interaction between teachers and student, make student more focus in learning. Success in learning is a very important thing. This success can be influenced by school environmental factors, environment family, And method learning Which implemented in mathematics learning.